(untitled) (Journal of Namibian Studies : History Politics Culture, 2021)
Modern globally effective nosocomially significant. Necessary actions to reduce this phenomenon in everyday medical practice are included in WHO guidelines and include: systematic education and training of healthcare professionals; accurate infection surveillance; using problem solving or pilot groups including epidemiologists, microbiologists, and infection control nurses; improvements in hospital infrastructure, control and organization of infection prevention and control. An important element in preventing infections is the preparation and organization by hospitals of an infection control audit in their wards, consisting in testing the hospital infection preparedness and knowledge about infection control rights of healthcare professionals. Also, it is important to evaluate the knowledge of the medical staff and their adherence to the basic principles of hospital infection control, in particular among young medics and medical students, as a group at high risk of infection. It was suggested in the meta-analyses of the students’ knowledge and skills in infection control that over time, more knowledge is retained and web-based learning is often more effective ([ref: 8af385bd-7583-466b-b0c3-aea0c0e1b703),. Infections transmitted from the healthcare environment to patients and healthcare professionals are a significant health problem. It is estimated that 8.7% of patients in Europe suffer from health-care associated infections, and these infections have a significant impact on morbidity and mortality of patients mentioned in (B Khanagar et al., 2020). Healthcare professionals become infected and sick as well and are often in contact with an extended network of contacts (Iuliana Bocicor et al., 2020). Reducing the prevalence of nosocomial infections begins with upgrading the infection control strategy in healthcare settings and assessing the knowledge of healthcare professionals regarding the principles of hospital infection control. There are many quite effective methods, such as teaching healthcare professionals in hospitals. However, an innovative approach is, for example, the use of mobile devices in teaching students in the field of health sciences ( (Yoshikawa et al., 2021